EFEKTIVITAS PENGGUNAAN METODE MIND MAPPING TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN GEOGRAFI KELAS XI - Rosita, Rosita; Sulistyarini, Sulistyarini; Anasi, Putri Tipa (Universitas Tanjungpura, 2024)
This research aims to determine the learning outcomes of students before and after using the Mind Mapping method, identify the differences in learning outcomes before and after using the Mind Mapping method, and assess the effectiveness of the Mind Mapping method on the learning outcomes of students in class XI IIS A in geography education at MA Khulafaur Rasyidin. The research type used is a pre-experimental design. The research design employed is the One Group Pretest-Posttest design, where the experimental research is conducted without a control group. Sampling was determined using purposive sampling by selecting class XI IIS A as the experimental group, consisting of 41 students. Data collection techniques used in the research include tests, documentation, observation, and interviews. The research instruments are test sheets, observation sheets, documentation, and interview guidelines. The results show that the average scores before and after using the Mind Mapping method are 46.98 and 72.59, respectively. This is supported by the non-parametric statistical test results using the Wilcoxon Signed Rank Test, which yielded an Asymp. Sig. (2-tailed) of 0.000 0.05, indicating that the hypothesis is accepted, meaning there is a significant difference in geography learning outcomes between the pretest and posttest. Additionally, the effect size calculation yielded a value of 2.02, classified as high according to effect size calculations, indicating that the Mind Mapping method is effective for use, as it helps students understand the material more quickly.